Uji Efek Antiinflamasi Fraksi Air Daun Mahkota Dewa (Phaleria macrocarpa (Shecff.) Boerl.) terhadap Tikus Putih (Rattus norvegicus L.) - Eff, Aprilita Rina Yanti; Dewanti, Ema; Adelina H, Melisha (Pharmaceutical Sciences and Research, 2014)
Inflammation occurs as the attempt of body to inactivate organisms that attack the body, removing irritants and regulate tissue repair. One of the medicinal plants used empirically as antiinflammation is the leaf of Mahkota Dewa (Phaleria macrocarpa (Schecff.) Boerl). This study investigated the effect of anti-inflammatory water fraction of leaf Mahkota Dewa using oedema induction method with caragenin in rat. Water fraction of Mahkota Dewa was given at the dose 0.5 g/kg BW ,1 g/kg BW and 2 g/kg BW. Sodium diclofenac was used as a positive control and CMC as negative control. The result showed water fractions of three doses can inhibit inflammation at 27.35%, 18.58%, and 20.17%, respectively. The water fraction at the dose 0.5 g/kgBW showed the largest percentage of oedema inhibition compared to other treatment groups.